ChatGPT as a Data Scientist: Can AI Handle Clustering Better Than a Human? - Lemesev, Alexandru (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence